DNA related enzymes as molecular targets for antiviral and antitumoral chemotherapy. A natural overview of the current perspectives - Garro, Hugo Alejandro (2019)
Background: The discovery of new chemotherapeutic agents still remains a continuous goal to achieve. DNA polymerases and topoisomerases act in nucleic acids metabolism modulating different processes like replication, mitosis, damage repair, DNA topology and transcription. It has been widely documented that Polymerases serve as molecular targets for antiviral and antitumoral chemotherapy. Furthermore, telomerase is a ribonucleoprotein with exacerbated activity in most of the tumor cell lines, becoming as an emergent target in Cancer treatment. Methods: We undertook an exhaustive search of bibliographic databases for peer-reviewed research literature related to the last decade. The characteristics of screened bibliography describe structure activity relationships and show the principal moieties involved. This work tries to summarize the investigation about natural and semi-synthetic products with natural origin with the faculty to inhibit key enzymes that play a crucial role in DNA metabolism. Results: Eighty-five data references were included in this review, showing natural products widely distributed throughout the plant kingdom and their bioactive properties such as tumor growing inhibitory effects, and anti-AIDS activity. Conclusion: The findings of this review confirm the importance to find new drugs and biologically active natural products, and their potential medicinally useful benefits.